Influence of the inlet flow swirler construction on hydrodynamics and efficiency of work - Pitak, Inna; Briankin, Serhii; Pitak, Oleg; Shaporev, Valery; Petrukhin, Serhii (Technology audit and production reserves, 2017)
The object of research is construction of a vortex dust collector. To solve the problem of increasing the efficiency of dust cleaning in a vortex apparatus with revealing the features of the mechanism and the destructive forces of the process, the features of the hydrodynamic regime of rotation of the gas-dust flow in the zone of the swirler and immediately after it are used. The influence of the swirler construction and the location of its installation in the gas duct for feeding the gas-dust flow on the efficiency of the vortex apparatus is studied. It is shown that the aerodynamic processes that determine the nature of the flow rotation and its flow in the flue after the swirler reach the maximum possible angular velocity of the gas flow rotation in the separation chamber for this construction. It is proved that the swirler construction under the appropriate conditions allows a swirling flow leaving the duct to the separation chamber to reach the maximum possible angular velocity of the gas flow rotation for the given construction. The characteristic regimes of the gas-dust flow in the duct are established immediately after the swirler from its construction. It is shown that for a traditional vane swirler with a swirling flow in one direction, the most effective blade inclination angle corresponds to 45°. Its installation must be carried out in the duct from the end outlet to the separation chamber below by 1.4¸1.6 of the swirler diameter. Before the gas-dust flow flows into the separator, the flow is agglomerated with dust particles. At the exit of the gas-dust flow from the end of the flue to the separation space, the maximum value of the angular velocity of the flow in the separator is ensured. It is established that the blade vortex, which provides for the organization of coaxial turbulent flows in the flue, twisted in opposite directions, will allow more efficient agglomeration of dust particles. A basic construction of the vortex dust collector is developed, which makes it possible to increase the cleaning efficiency with a vortex device to 98–99 %.